O estudo de frações em seus diferentes contextos: um diagnóstico com alunos de 6º ano da rede municipal de ensino de alto santo – ce - Gomes, Antônio Eclésio Martins (2019)
Educational studies, especially the ones that refer to Mathematics education, have widely discussed teaching/learning of fractions in Elementary School on the subject of difficulties showed by students. This study aims to diagnose the essence of the obstacles of learning fractions and to propose a series of didactic activities that may resolve the problem of learning the mentioned content. The research is a quantiqualitative study based on action research. The study uses knowledge from general readings on the subject in texts, articles, dissertations, and books. Fractions are present in our daily lives and sometimes are not perceived. They are deeply connected to several situations we experience. That being said, the insertion of the study of fractions in Elementary School is considered of extreme importance for the sequence of contents reserved to the final years of Elementary School and High School. As a methodological instrument, diagnose tests were applied to 6th-grade students in the town of Alto Santo in the State of Ceará in order to investigate the main problems in the teaching/learning of fractions. After analysis of the answers from the participants, we proposed the application of an interventive didactic set of activities aiming to decrease students’ difficulties. Results showed that most students have problems when relating a rational number to its diverse representations and that they are not able to locate correctly a rational number on a number line. The conclusion states that there are and there will be obstacles in the process of teaching/learning fractions as well as the fact that they are extremely important in our daily basis. It is only possible to obtain success in the learning of Mathematics when there is a union between teachers and students. In the academic world, many barriers appear. The necessity of trespassing them is what makes us going forward